WENCESLAU BRAZ E A POLÍTICA CAFÉ COM LEITE: Estratégias de comunicação e marketing político que o elegeram Presidente da República do Brasil - Victorino, Juliana Leone Paiva (2012)
This study portrayed the process of communication and political marketing in the public life of Wenceslau Braz, president of Brazil from 1914 to 1918. She approached the Brazilian policy of that time and showed the strategies of persuasion used to indicate the position of the miner, showing how the press at the time reacted in this election period. The methodology that guided this dissertation was to "Case Study", based on the basics of Robert Yin, where several studies were conducted bibliographic, documentary and interviews with family and friends of Wenceslas. In addition four of the Brazilian press publications were analyzed. It is concluded that the participation of the press was quite irrelevant in this process and the electoral process was dictated by the political regime of the time.